Real time bus tracking system - Muhammad Addeib, Mohd Subari (2019)
Rapid Kuantan is a bus brand owned by Prasarana Malaysia Berhad to conduct bus services in Kuantan, Pahang, Malaysia. When travelling in buses, public want to know their exact arrival time because sometimes the bus schedule does not have the reliability in terms of punctuality. One of the main problems is the bus’s user did not know the exact time of the arrival bus. Bus management only provide bus’s timetable for the user. The bus’s user needs to go out earlier to the bus stop to wait for the bus. This is because they did not want to miss the bus that they target at the bus’s timetable. Sometimes, the bus’s user needs to wait for too long for the arrival bus because they did not know the exact time the bus will arrive and when they want to chasing time for the certain reason they will become angry. By wasting a lot of time waiting for the bus, that time actually can do something else beneficially. The main objective is to apply GPS tracking technology into bus transportation system. This is to propose to the bus admin to install the Bus Tracking System application that able to track the actual position of the bus. Next, this application will be sending position data of the bus to database and the data will be display as moving bus icon on the map. Next objective is to provide the exact location of the moving working bus. The exact location will help user to manage their time for not waiting too long for the bus. Real Time Bus Tracking System was developing by using Rapid Application Development (RAD) methodology. It is because this method can make rapid development process. This application will be used by many people in the future. The benefits of this application are it can reduce bus waiting time and help people to set what time they will arrive at destination.